Pengaruh Pemberian Aktivitas Leisure Terhadap Tingkat Kualitas Hidup Pasien Pasca Stroke - Wawan Ridwan Mutaqin; Ninik Nurhidayah (Poltekkes Kemenkes Surakarta, 2017)
Abstrack : Leisure Activities, Quality Of Life, Stroke. Stroke can cause impairment, disabilities and handicap so that patients will have difficulty in performing daily life activities, including self-care, productivity and leisure. It will cause decrease the patient quality of life. This study aims to determine the effect of leisure activities on the quality of life of Post-Stroke Patients. This study is an experiment with methods of the one group pretest-posttest design. Sampling was done by purposive sampling, with the number of samples of 25 stroke patients, at Ngemplak Boyolali District. The results showed that there was a possibility of the activity of leisure activity on the quality of life Post Stroke, significantly with the value of p = 0,002 (physical health), p = 0,001 (psychological), p = 0,001 (social relation), and p = 0,000 (environment). Based on age, the number of respondents is the final elderly of 11 people (44%), male sex is 16 people (64%), marital status 20 people (80%) married / have spouse, most respondents are 8 people 32%) did not work, and large respondents suffered stroke over 24 months as many as 10 people (40%). The implication of this research is that leisure activities can be used as an alternative method in the treatment of occupational therapy in stroke patients